Gambling on a Sale: Gift-enterprise Bookselling and Communities of Print in 1850s America - Highland, Kristen (Knygotyra, 2022)
This article explores the phenomenon of the gift enterprise bookstore in the mid-nineteenth-century United States. An early form of premium marketing, the gift-book enterprise promised to reward each book purchase with a surprise ‘gift’, ranging from pencils to dress patterns to cutlery to jewellery. A novel form of marketing books, the gift enterprise bookstore teetered on a thin line between sensation and sham. Although decried as form of illegal lottery gambling and beset by accusations of dishonesty, gift-book enterprises grew immensely popular. Drawing on extensive archival research on one of the most successful gift-book enterprises, the bookstores of G.G. and D.W. Evans—operating in urban centres from 1856–1861—this article examines gift enterprise bookselling in the context of mid-nineteenth-century American print cultures. As savvy entrepreneurs, the Evans’ leveraged the national reach and perceived authority of the newspaper by engaging in debates over the morality and legality of the business in the columns of widely-circulating papers and capitalised on editorial and reprinting practices to endorse their business model and market their bookstores. In addition, in lengthy bookseller catalogues distributed across the nation, the Evans’ created a bookstore in print and shaped inclusive imagined and real communities of reader-book buyers. Examining the print culture of Evans’ gift-book enterprise offers new insights into nineteenth-century book marketing and the ways in which gift enterprise bookselling was intimately connected to and inseparable from contemporary print forms, networks, and practices. Taking the gift-book enterprise seriously expands the histories of American bookselling and decentres the dominant focus on large publishers. In addition, the gift-bookstore phenomenon highlights how bookselling is always entwined with larger cultural dynamics.